Implementasi Kebijakan Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK) di Kabupaten Jember - Ulfa Dwi Arizka (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
The health status of the people in Indonesia must be increase with program named PIS-PK. To be categorized in a healthy family, IKS (Healthy Family Index) has a standard of 0.8. Until now, the IKS in Indonesia still at 0.19 and the IKS in Jember Regency is still at 0.08. This study aims to analyze the implementation of PIS-PK policy in Jember Regency with study case research. The research was conducted at the Jember District Office, Jelbuk Public Health Center, and Gladak Pakem Public Health Center. The presentation of data is a narrative and validated by triangulation techniques. This research using four factors from Edward III's theory, namely communication, resource, disposition, and bureaucratic. The result showed that on the transmission factor has been running according the policy although there had a miss communication. On the resource factor, the needed for running program is appropriate although there are obstacles in the application which is used to input data that causes incompatibility of the input data and delays. Disposition factor, there had obstacles related to differences in operational definitions that made in confusion for implementors. The bureaucratic factor, there is no SOP for the implementation of PIS-PK in each public health center. Therefore, the Jember District Health Office is expected to be able to monitoring and evaluation in the implementation of PIS-PK. Then the advice given to Public Health Centers throughout Jember Regency is Public Health Center is expected to make SOPs, monitor and evaluate, use data from PIS-PK results properly, and the PIS-PK coordinator can coordinate well with all PIS-PK coordinators.